Characteristics and determinants of child malnutrition in Mozambique, 2003-11 - José Cardoso; Lindsey Allwright; Vincenzo Salvucci (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Child malnutrition continues to be a serious impediment to development both at the individual and national levels in many developing countries. In Mozambique, despite a high and sustained GDP growth, child malnutrition has been decreasing at a rather slow pace over the past 15 years. In this study, using the Mozambican Demographic and Health Surveys 2003 and 2011 we find that household wealth, mother's education, area of residence, and access to safe water and improved sanitation facilities have a strong relation with different measures of chronic child malnutrition. Also, the relative importance of these variables remained mostly unchanged over time. We conclude that continued and more focused and effective interventions aimed at directly reducing child malnutrition should be undertaken by all public and private actors involved.
Keywords: I15; J13; O15; 330; child malnutrition; stunting; Demographic and Health Survey data; Mozambique